How can the harvest method impact the seed quality of common bean with indeterminate growth habit? - Rafael Mateus Alves; Júlio César Altizani-Júnior; Josué Bispo da Silva; Francisco Guilhien Gomes-Junior (Pesquisa Agropecuária Tropical)
Despite the economic and social significance of common bean (Phaseolus vulgaris L.), the national yield remains limited, partly due to crop establishment issues related to low seed quality. This study aimed to evaluate the seed quality of the TAA Dama cultivar (type III, with indeterminate growth habit) harvested using manual, semi-mechanized and mechanized methods. The seed quality was assessed using germination, accelerated aging, seedling emergence, electrical conductivity, computerized seedling image analysis, sodium hypochlorite (mechanical damage) and X-ray test. The semi-mechanized and mechanized harvest methods proved suitable for seeds from plants with indeterminate growth habit, provided that harvest parameters are properly adjusted. However, the presence of hard seeds, particularly in the manually-harvested lot, negatively affected the germination speed and seedling development. The radiographic imaging was effective in detecting internal seed damage, complementing the conventional quality assessments.